Analysis of the Automotive Practice Ability in Terms of Understanding the Physics Students of Vocational High School - Laili, Nihla Nurul; Putra, Ngurah Made Darma; Astuti, Budi (Journal of Innovative Science Education, 2019)
Physics has become the foundation of vocational competence of vocational high school or Sekolah Menengah Kejuruan (SMK) in technology and engineering expertise. This research aimed to find out the ability of automotive practice in terms of the understanding of physics students SMK skills competency in Light Vehicle Engineering or Teknik Kendaraan Ringan (TKR). This study was a qualitative research with the subjects of this research were students grade X of TKR class at three SMK in Pekalongan. The data were collected by conducting the library research, test, interviews, and documentation. The data obtained were analyzed qualitatively descriptive. The results of library research analysis on the physics basic competence of SMK curriculum 2013 with the TKR basic competence show thirteen relevant physics material and one physics material not relevant to the basic competencies of TKR. Physics material that is irrelevant is straight and circular motion. The results of the physics tests of students in three SMK are still low, while the value of students' automotive practices is in the good category. This shows that students' physical abilities have not become the basis for learning automotive practices.